Cabaud Memorial Award: Lateral Extra-articular Tenodesis Alters Regional Distribution of Contact Stress in the Lateral Knee Compartment under Simulated Pivoting Loads: An In Vitro Study. Issue 7 (31st July 2020) - Ouanezar, Herve; Jahandar, Hamidreza; Zayyad, Zaid; Fraychineaud, Thomas; Hurwit, Daniel; Imhauser, Carl; Wickiewicz, Thomas; Pearle, Andrew; Nawabi, Danyal; Marom, Niv
Objectives: Residual laxity after ACL reconstruction (ACLR) may adversely impact patient outcomes and function and has led to the increasing utilization of lateral extra-articular augmentation procedures in conjunction with ACLR and specifically, Lateral Extra-articular Tenodesis (LET). However, concerns of overconstraining the lateral compartment and subsequent increased lateral compartment contact stress and accelerated degenerative changes have been suggested with LET procedures. Therefore, the purpose of this work was to assess the impact of a LET on contact mechanics of the lateral compartment in response to multiplanar torques representing pivoting maneuvers. Methods: Nine cadaveric knees (4 male, 37.4 ± 11.6 years old) were mounted to a robotic manipulator equipped with a six-axis force-torque sensor. The robot applied multiplanar torques simulating two types of pivot shift (PS) maneuvers, subluxing the lateral compartment, at 30° of knee flexion. The following loading combinations were applied: (PS1) 8 Nm of valgus and 4 Nm of internal rotation torques; (PS2) 100 N compression force, 8 Nm valgus torque, 2 Nm internal rotation torque, and 30 N anterior force. Kinematics were recorded in the following states: ACL intact, sectioned, reconstructed and, finally, after sectioning the anterolateral ligament (ALL) and kaplan fibers and performing a LET. ACLR was performed utilizing a bone-patellar tendon-bone autograft, via medial parapatellar arthrotomy. LET was performed using a modified lemaire technique with a metal staple femoral fixation at 60° of flexion in neutral rotation. A contact stress transducer was then sutured to the tibial plateau beneath the menisci and the previously-determined kinematics were replayed, while recording the lateral compartment contact stress. At the peak applied loads, the following measures were determined in the lateral compartment: contact force, contact area, the anterior-posterior (AP) location of the center of contact stress (CCS), the mean contact stress, and the peak contact stress and its AP location. Statistical differences were assessed via one-way repeated measures ANOVA with Student-Neumen-Keuls post hoc test (p< 0.05). Results: Under combined valgus and internal rotation torques (PS1), the addition of a LET to ACLR increased lateral compartment contact force compared to the native knee by 51 ± 51 N (p = 0.035) on average. Contact area also increased by 60 ± 56 mm2 and 61 ± 58 mm2 relative to the ACL intact and ACL reconstructed knee (p ≤ 0.002), respectively. LET also shifted anteriorly the CCS by 4.6 ± 3.6 mm and 5.7 ± 3.1 mm on average relative to the ACL intact and ACL reconstructed knees (p < 0.001) (Fig. 1). No differences were detected for the mean and peak lateral compartment contact stress with the addition of LET compared to the ACL intact or ACL reconstructed knee (p> 0.854). The location of peak contact stress, however, shifted anteriorly compared to the ACL intact and ACL reconstructed knees by 6.2 ± 5.7 mm and 7.6 ± 5.4 mm (p < 0.001). (Fig.1). Similar results were observed under multiplanar torques with compression (PS2) for all outcome measures. Conclusion: In response to multiplanar torques representing pivoting maneuvers, the addition of a LET to ACLR, in the presence of compromised anterolateral tissues, did not increase lateral compartment contact stress. As contact force increased with the addition of LET, so did the contact area, likely mitigating changes in the level of contact stress. LET shifted the contact location anteriorly thereby altering regional loading of the lateral articular cartilage. Further study of the impact of changes in regional loading patterns in the lateral compartment on cartilage degeneration is warranted. Figure 1.